Criticism of Colonialism in Serat Kridawasita: A Postcolonial Study of Traditional Javanese Literature - Anugrah Putri Juniarti; Adi Sasongko Romadhon (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
Serat Kridawasita is one of the traditional Javanese literary works that contains criticism of colonialism. This article aims to examine how Serat Kridawasita constructs a discourse of resistance against colonialism through a postcolonial theory approach. The analysis focuses on symbolism, colonial representation, and forms of cultural resistance contained in the text. The results of the study show that Serat Kridawasita becomes an ideological space where identity, nationalism, and veiled criticism of colonial hegemony are affirmed. This study confirms that traditional literature is not merely a moral medium, but also an ideological tool of struggle.